Bridging Students and Lecturer's Expectation in Learning Process through Self Assessment - Muhimatul Ifadah; Siti Aimah (Universitas Muhammadiyah Semarang, 2017)
This study was aimed to describe student- lecturer expectation in the process of learning. The students and lecturer were given questionnaire which revealed their difficulty for lessons they enrolled. For the teacher, they were asked to describe their expectation to their students and describe the teaching; the preparation, process, and evaluation. The result showed that most of the students concern about the lecturers approach and methodology. 92% of sixty two students wrote that final score is very important, and it was the teacher who has the main role to transfer the comprehension. However, 8% students wrote that each of them should have their own strategies in learning the subjects, because each lesson will not have the same difficulty. In addition, someof them are also delivering that personal problem sometimes become more disturbing than the subject itself. Media becomes an alternative in eliminating the boredom and the anxiety in comprehending the lesson. It also can be said that the lecturers have different way in indicating the success of learning, 60 % indicated success with the students improvement and behavior, the rest wrote that successful learning is whenever the students able to perform what is demanded on the lesson, for example a product. Almost all of the students said that it was very helpful if the lecturer can be open-minded to the students about the evaluation, particularly- on what base the final score is resulted. Though, some lecturers also describe that they adjust the evaluation from the assignment, examination, and also the manner.